REDUCING ENERGY CONSUMPTION IN IOT BY A ROUTING WHALE OPTIMIZATION ALGORITHM - Heidari, Ehsan; Movaghar, Ali; Motameni, Homayun; Barzegar, Behnam (Malaysian Journal of Computer Science, 2022)
The Internet of Things is a new concept in the world of information and communication technology, in which for each being (whether it be a human, an animal or an object), the possibility of sending and receiving data through communication networks such as the Internet or Intranet is provided. Wireless sensors have limited energy resources due to their use of batteries in supplying energy, and since battery replacement in these sensors is not usually feasible, the longevity of wireless sensor networks is limited. Therefore, reducing the energy consumption of the used sensors in IoT networks to increase the network lifetime is one of the crucial challenges and parameters in such networks. In this paper, a routing protocol has been proposed and stimulated which is based on the function of the whale optimization algorithm. Clustering is performed through a routing method which is based on energy level, collision reduction, distance between cluster head node and destination, and neighbor energy. Furthermore, the selection of the cluster head node is performed based on the maximum remaining energy, the least distance with other clusters, and energy consumption, where energy consumption for reaching the base station is minimized. By de-creasing the level of cluster head energy from the specified threshold value from among the nodes in the same cluster, a node with an energy level above the threshold would be selected as the new cluster head. Moreover, four conditions (i.e. the shortest route, the leading route, the least distance to the source node, and destination node) are applied for routing. The proposed method was compared to LEACH, EEUC, EECRP, BEAR and CCR algorithms, and the results indicated the superiority of the proposed method to other methods in terms of the number of dead nodes.